The Puzzling Issue of 'Vehicle‐Treated Control' when Using Ethanol as Drug Carrier for MCF‐7 Cells. (9th April 2014) - Chan, Robbie Yat‐Kan; Lee, Kenneth Ka‐Ho; Wong, Wai‐Yeung; Tang, Johnny Cheuk‐On; Lam, Kim‐Hung; Cheng, Chor‐Hing; Lau, Fung‐Yi; Kok, Stanton Hon‐Lung; Gambari, Roberto; Chui, Chung‐Hin
<x xml:space="preserve">Abstract</x> Ethanol has been commonly used as a vehicle for drug discovery purpose in vitro. The human breast cancer MCF‐7 estrogen dependent cell line is a common in vitro model used for hormonal therapy study. However, special precaution is suggested when ethanol is used in pharmacological tests as solvent in order to evaluate the biological activity of potential drugs especially concerning about the MCF‐7. Ethanol was shown to stimulate the proliferation of this estrogen receptor positive cell line. Here, we have further demonstrated that the dose responsive stimulatory effect of ethanol on the MCF‐7 cells after pre‐incubating the breast carcinoma cells with phenol red‐free medium and stripped fetal bovine serum. Our findings open a discussion for the evaluation of ethanol as solvent for drug discovery and screening when using MCF‐7 cells as a testing model. Copyright © 2014 John Wiley & Sons, Ltd.